Serological prevalence of leptospiral infection in domestic animals in West Malaysia - Bahaman, A. R.; Ibrahim, A. L.; Adam, H. (Cambridge University Press, 1987)
A cross-sectional serological survey of domestic animals in West Malaysia revealed that 25·5% of the animals examined had agglutinating antibodies to one or more antigens belonging to Leptospira interrogans. Significant prevalence of infection was observed in cattle (40·5%), buffaloes (31%) and pigs (16%). The Sejroe serogroup was shown to be the principal one involved in cattle and buffaloes, and to a lesser extent the Tarassovi and Pomona serogroups. Evidence of infection in domestic animals by strains bearing the other seven antigens appeared insignificant and was indicative of sporadic infection. A majority of the large (semi-intensive) cattle and buffalo farms demonstrated a high prevalence of leptospiral infection. In both species of domestic animals mentioned above, the prevalence of infection was significantly higher (P = 0·01) in the semi-intensive farms than in the smallholdings. Amongst cattle, the droughtmasters had the highest prevalence whilst the Kedah-Kelantan (an indigenous breed) had the lowest prevalence of leptospiral infection. In general, the temperate breeds of cattle had a significantly (P = 0·01) higher prevalence of infection than local breeds. Leptospiral infection in goats and sheep was shown to be sporadic, and the Pomona serogroup was the principal leptospiral serogroup involved in these small ruminants. The prevalence of infection in pigs was observed to decline during the study period, and it is suspected that pigs in West Malaysia are the maintenance host for serovar pomona whilst cattle are the maintenance host for serovar hardjo. Overall, it appears that domestic animals in Malaysia will play a bigger role in the epidemiology of leptospiral infection with the advent of sophisticated farming.